2019
DOI: 10.2147/ijn.s208332
|View full text |Cite
|
Sign up to set email alerts
|

<p>Curcumin-loaded nanoparticles: a novel therapeutic strategy in treatment of central nervous system disorders</p>

Abstract: Curcumin as a hydrophobic polyphenol is extracted from the rhizome of Curcuma longa. Curcumin is widely used as a dietary spice and a topical medication for the treatment of inflammatory disorders in Asia. This compound also possesses remarkable anti-inflammatory and neuroprotective effects with the ability to pass from the blood brain barrier. Based on several pharmacological activities of curcumin, it has been introduced as an ideal candidate for different neurological disorders. Despite the pleiotropic acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
147
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 254 publications
(150 citation statements)
references
References 95 publications
(101 reference statements)
1
147
0
2
Order By: Relevance
“…Additional information regarding pharmacokinetic studies and enzymatic hydrolysis are provided below. In addition to the above commercial formulations, a wide range of micellar and nano-particle formulations of curcumin have been prepared involving the use of ingredients as Tween 80, polysorbate 80, ceramic particles, polyethylene glycol (PEG), alginate, poly(lactic-co-glycolic acid) (PLGA), omega-3 fatty acids, chitosan and other substances [38][39][40][41][42]. Chemically modified variations of curcumin as well as conjugates in addition to the above formulations have been also developed.…”
Section: Formulation Strategiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Additional information regarding pharmacokinetic studies and enzymatic hydrolysis are provided below. In addition to the above commercial formulations, a wide range of micellar and nano-particle formulations of curcumin have been prepared involving the use of ingredients as Tween 80, polysorbate 80, ceramic particles, polyethylene glycol (PEG), alginate, poly(lactic-co-glycolic acid) (PLGA), omega-3 fatty acids, chitosan and other substances [38][39][40][41][42]. Chemically modified variations of curcumin as well as conjugates in addition to the above formulations have been also developed.…”
Section: Formulation Strategiesmentioning
confidence: 99%
“…Chemically modified variations of curcumin as well as conjugates in addition to the above formulations have been also developed. However, no pharmacokinetic studies have been reported to demonstrate the improvement in absorption and bioavailability [38][39][40][41][42]. As a consequence, only limited claims for greater bioavailability and efficacy can be justifiably made.…”
Section: Formulation Strategiesmentioning
confidence: 99%
See 3 more Smart Citations